Nghiên cứu và ứng dụng hệ thống xung điện trở dòng chỉnh lưu rôto động cơ không đồng bộ rôto dây quấn cho các thiết bị nâng hạ - Nguyễn, Như Hiển (Bộ Giáo dục và Đào tạo, 2013)
Through studying the new scientific achievement in electric, electronic and automation, the report presents the application of the resistor - impulse system erctifying the current in coil rotor of the three - phase (asynchronous) motor of the lifters in some factories belonging to Thai Nguyen Steel and Iron Company .